Romska slovnica ruskega kelderarskega narečja - Elšík, Viktor (Slavia Centralis, 2024)
The contribution aims to draw attention to a recently published grammar of the Russian Kelderar dialect of Romani (Oslon 2018), the most detailed description of any Romani variety to date. After introducing the dialect described, the paper characterizes the grammar in terms of its sources and representation of data, its structure, and its attention to synchronic variation and diachrony, including language contact; it highlights selected innovative analyses; and discusses two debatable analyses. The paper concludes that Oslon’s grammar could become a model for Romani grammaticography.
Keywords: Romani language, Russian Kelderar dialect, grammatical description, grammaticography